The Authority of Judicial Review on the Administrative Court Decision No. 234/G/2024/PTUN.JKT: A State Administrative Law Perspective - Sirait, Timbo Mangaranap; Khalimi; Halim, Adriasnyah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The Jakarta Administrative Court's decision declaring the lawsuit inadmissible due to the absence of a state administrative decision as the object of the dispute illustrates the narrow limits in interpreting the authority of administrative courts. Administrative law should provide protection for citizens' rights against administrative negligence, the lawsuit was rejected because it was deemed not to meet the formal elements in the PTUN procedural law. This study aims to determine how the PTUN's authority is in adjudicating lawsuits regarding state officials' negligence against citizens' constitutional rights, as in Decision Number 234/G/2024/PTUN.JKT and whether the Supreme Court can conduct a judicial review of the PTUN's decision that rejected the lawsuit because the object of the dispute was deemed not to meet the requirements of state administrative law. This research is normative juridical using secondary data. The results of this study indicate that the PTUN has the authority to adjudicate lawsuits regarding state officials' negligence if they relate to state administrative actions that harm citizens' administrative rights, although it often limits its authority formally. The Supreme Court can conduct a judicial review of the PTUN's decision that rejected the lawsuit because the object of the dispute did not meet the requirements of administrative law, by focusing on the legal aspects and the PTUN's authority, without re-evaluating the facts.